Urinary Canthariasis Due to Tenebrio molitor Larva in a Ten-Year-Old Boy - Mohammad Hassan Aelami; Alireza Khooei; Hamidreza Ghorbani; Farrokh Seilanian-Toosi; Elham Poustchi; Bibi Razieh Hosseini-Farash; Elham Moghaddas (Tehran University of Medical Sciences, 2019)
Canthariasis is a human disease caused by infestation of beetle larvae. We report here an unusual cause of urogenital infection due to Tenebrio molitor in a 10-year-old boy suffering from severe and intermittent suprapubic pain from Nehbandan City, Northeastern Iran in 2018. After 9 months, three larvae were excreted. Keratinization of bladder wall was observed in histopathology. All laboratory evaluations were normal except for presence of microscopic hematuria. This report implicated that T. molitor could infest bladder accidentally and cause canthariasis and clinical symptoms that may lead to severe pain and bladder inflammation and hyperemia.